2006
DOI: 10.1021/ja061664x
|View full text |Cite
|
Sign up to set email alerts
|

Regioregular Copolymers of 3-Alkoxythiophene and Their Photovoltaic Application

Abstract: Low band gap conjugated polymers with proper energy levels for charge transfer are required to achieve high-efficiency polymer solar cells. We report the synthesis and characterization of two new regioregular copolymers that are based on 3-alkoxythiophene monomers: poly(3-octylthiophene-2,5-diyl-co-3-decyloxythiophene-2,5-diyl) (POT-co-DOT) and poly{(9,9-dioctylfluorene)-2,7-diyl-alt-[4,7-bis(3-decyloxythien-2-yl)-2,1,3-benzothiadiazole]-5',5' '-diyl} (PF-co-DTB). Compared to the alkyl substituents, the alkoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
210
2
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(219 citation statements)
references
References 38 publications
6
210
2
1
Order By: Relevance
“…A closely related polymer (28) with O-alkyl side chains on the thiophene rings of 27 was synthesized by Pei and coworkers. [18] PCE of 1.6% was obtained for the device with 28…”
mentioning
confidence: 89%
“…A closely related polymer (28) with O-alkyl side chains on the thiophene rings of 27 was synthesized by Pei and coworkers. [18] PCE of 1.6% was obtained for the device with 28…”
mentioning
confidence: 89%
“…It is reasonable to believe that the P3DT/N/TiO 2 nanocomposite will perform better in semiconductors than P3DT and N/TiO 2 . Using the Equations (1) and (2) [19,20]:…”
Section: Uv-vis Spectra Of N/tio 2 P3dt and P3dt/n/tiomentioning
confidence: 99%
“…Their photovoltaic effect has been widely used in polymer solar cells and dye-sensitized solar cells. [16][17][18][19][20][21][22] By combining their electrocatalytic activity and photophysical properties, conducting polymers have become efficient light-enhanced catalysts for ORR in more recent research works. [23][24][25] Winther-Jensen and co-workers demonstrated that an "alloy" of PEDOT and polythiophenes shows electrocatalytic activity towards ORR.…”
mentioning
confidence: 99%